Повести: перевод с английского / Френсис Бернетт - Бернетт Френсис Элиза (Русская книга, 1992)
Экземпляры: ф.2 (1993) / Инвентарный номер: 36908 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: Б 51 / ГРНТИ: 17.82.93 / ББК: 84(7Сое)-44